Ichthyoplankton in the Pánuco river estuary, Tamaulipas-Veracruz - Sánchez-Ramírez, Marina; Ocaña-Luna, Alberto; Berrios-Zamudio, Ariana Lizbet (Ecosistemas y Recursos Agropecuarios, 2021)
To determine the structure of the ichthyoplankton assemblage along a saline gradient in the Pánuco river estuary, sampling was performed in: January, March, May, July, September, and November in 2017 at nine sites, with a standard network with a mesh opening of 500 μm. 1 165 eggs and 526 fish larvae were collected from 18 species, three of them from freshwater. The highest specific richness was observed in the middle estuary and lagoon of Pueblo Viejo. The highest values of diversity and evenness was found in November (2.7 and 0.9, respectively). The dominance was greatest in July (0.4) due to the abundance of Anchoa mitchilli. The ichthyoplankton assemblage was characterized by a greater number of dominant marine and estuarine species, a low number of freshwater species and a decrease in species richness upstream.